Quantifying kinematic and coordinated movement patterns during pumping in windsurfing: the impact of footstraps use - Chun, S.; Park, J. (Korean Journal of Sport Biomechanics, 2025)
Objective: In windsurfing, pumping is the only technique for propulsion, and the use of footstraps (FS) contributes to control of the board. Deep knowledge in this area can help achieve efficient movements and provide evidence-based coaching. This study investigated the impact of FS use on limb kinematics and coordination during pumping in windsurfing. Method: Three male national windsurfers performed pumping in both FS and non-footstraps (NS) conditions on water. Kinematic data were collected using 11 inertial measurement units, attached to the participants' limb segment. The time taken, range of motion (ROM), angles (hip, knee, shoulder, and elbow joints), angular velocities, and continuous relative phase (CRP) were analyzed on the sagittal plane. Results: During pumping, the elbow joint exhibited contrasting kinematic characteristics in terms of joint angles and angular velocities compared to the hip, knee, and shoulder joints. CRP was observed in-phase coordination among between hip, knee, and shoulder joints, while anti-phase coordination was found between the elbow joint and the other joints. The FS condition showed greater hip and knee joint ROM, joint angles, and angular velocities, as well as reduced elbow joint ROM, and longer time spent during phase 2. Conclusion: We quantified the kinematics and CRP during pumping in windsurfing athletes under FS and NS. These results underscore the importance of the hip joint in pumping performance and suggest that the elbow joint exhibits coordination patterns that differ from those of other joints. Furthermore, the findings imply that the use of FS may enhance pumping performance by providing a more stable base, increasing lower limb mobility, and reducing reliance on the upper limbs. However, the generalizability of the findings and their explanatory power regarding pumping performance are limited due to the small sample size, the absence of direct speed measurements, and the use of qualitative methods.